Progressive Multifocal Leukoencephalopathy in an Immunocompetent Taiwanese Patient - Yung-Yee Chang; Min-Yu Lan; Cheng-Huei Peng; Hsiu-Shan Wu; DeChing Chang; Jia-Shou Liu (Journal of the Formosan Medical Association, 2007)
Progressive multifocal leukoencephalopathy (PML) is a deadly demyelinating brain disease caused by JC virus (JCV). Genomic analysis of viral isolates in these cases often shows prototype-like JCV and its variants, which is a virulent strain compared to the latent archetype virions mostly found in the kidney. Here, we report a 57-year-old man who suffered from a subacute course of cognitive impairment and multiple neurologic deficits. Neuroimaging, pathology, and virology studies showed multifocal leukoencephalopathy and the presence of JCV deoxyribonucleic acid in the cerebrospinal fluid. The prototype type 1 (Mad-1) strain of JCV was identified on viral genotyping obtained from brain tissue. No immune deficits were found. He responded poorly to a-interferon and antiviral treatment. This case suggests that lack of immune deficiency cannot exclude the possibility of PML as a cause of subacute leukoencephalopathy. Accumulated data with respect to the disease course, pathologic feature, and viral genomic subtyping may pave the way for future treatment against this devastating disease. [J Formos Med Assoc 2007;106(2 Suppl):S60-S64]